2016
DOI: 10.1039/c5gc01792k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a polyisobutylene-tagged fac-Ir(ppy)3 complex and its application as recyclable visible-light photocatalyst in a continuous flow process

Abstract: The facile synthesis and application of a polyisobutylene--polymer--tagged, iridium(III) photocatalyst is described. The catalytic performance of this complex remains consistently high, while the installed tether allows for its convenient separation from reaction products through a thermomorphic solvent system. Excellent recycling properties were observed both in batch and in flow reactions, and especially in the latter the continuous, automatic recovery and reuse of the catalyst either from a mono-- or a biph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 53 publications
0
71
0
2
Order By: Relevance
“…Two obvious issues are the batch nature of the reaction and the scarcity of rare earth metals, iridium in this case, that are used in the photocatalyst. First, we 11 and countless others 14,45 have demonstrated that almost any photo-HDF reaction can be transposed from batch to flow methodology, usually with improved kinetics. Second, given that the reaction is triggered by an electron transfer, it is likely that there are numerous other catalysts which could facilitate the photo-HDF reaction and relieve the iridium issue altogether.…”
Section: Resultsmentioning
confidence: 99%
“…Two obvious issues are the batch nature of the reaction and the scarcity of rare earth metals, iridium in this case, that are used in the photocatalyst. First, we 11 and countless others 14,45 have demonstrated that almost any photo-HDF reaction can be transposed from batch to flow methodology, usually with improved kinetics. Second, given that the reaction is triggered by an electron transfer, it is likely that there are numerous other catalysts which could facilitate the photo-HDF reaction and relieve the iridium issue altogether.…”
Section: Resultsmentioning
confidence: 99%
“…85 A polyisobutylene-polymer-bound iridium(III) catalyst was used to promote deiodination of alkyl iodides or E/Z isomerization of styrenes in a microreactor making use of a thermomorphic solvent system. 86 Here, a heptane/MeCN biphasic solution containing the photocatalyst (in heptane) and the reagents (in MeCN) was heated at 85 • C to have a homogeneous mixture. Irradiation of this system with blue LED light (λ = 455 nm) followed by cooling and phase separation allowed to isolate the products from the heptane phase containing the catalyst, that could be reused.…”
Section: Flow Photoreactor With External Irradiationmentioning
confidence: 99%
“…Irradiation of this system with blue LED light (λ = 455 nm) followed by cooling and phase separation allowed to isolate the products from the heptane phase containing the catalyst, that could be reused. 86 Flow photoreactors were also sparsely used in industry. An industrial plant consisting of twelve microreactor units operated in parallel was used in the production of anticancer 10-hydroxycamptothecin 49 from the corresponding N -oxide 48 on a kg-scale.…”
Section: Flow Photoreactor With External Irradiationmentioning
confidence: 99%
“…Reiser described an efficient application of a polyisobutylene-tagged Ir(ppy) 2 (PIB-ppy) photocatalyst in a continuousflow alkenes isomerization (Scheme 61) [84].…”
Section: Miscellaneous Casesmentioning
confidence: 99%